Assessment of nasopharynx area and level of severity posterior crossbite on children with cleft lips and palate post-palatoplasty - Apriani, Anie; Primarti, Risti Saptarini; Kasim, Alwin; Oscandar, Fahmi (Faculty of Dentistry Universitas Padjadjaran, 2020)
Introduction: Many children with post palatoplasty had crossbite posterior. This study was aimed to assess the nasopharynx area and the posterior crossbite severity level of children with cleft lip and palate (CLP) who received palatoplasty treatment compared to normal children. Methods: The study was observational analytic. The research subject was 14 children with CLP post-palatoplasty and 14 normal children. The object of research was 28 study models and secondary data of lateral cephalometric radiograph of children with CLP post palatoplasty and normal children. The measurement of PTM-ad1-Ad2-PTM and PTM-So-Ba-PTM were used to measure the nasopharyngeal area. Study models were assessed to analyse the level of severity of posterior crossbite. Results: The average of the soft tissues (the nasopharynx) area children with CLP post-palatoplasty was 35.02 mm2, which was lower than the normal child (35.73 mm2). Similarly, the average of the hard tissues (the nasopharynx) area children with CLP post-palatoplasty was 301.40 mm2, which was smaller than the normal children (315.54 mm2). Statistical analysis of the nasopharynx area resulted in non-significant difference. All children with CLP post-palatoplasty was suffered from posterior crossbite. The level of severity posterior crossbite, which was categorised as good was 42.9%, poor criteria was 35.7%, moderate criteria was 14.3%, and very good criteria was 7.1%. Conclusion: There is no difference between the average size of the nasopharynx area on children with CLP post-palatoplasty and normal children. The level of severity posterior crossbite after palatoplasty in CLP children mostly included in the good criteria.